Middle Paleolithic surface finds on the northern coast of the Taganrog Bay - Kolesnik A.V.; Danilchenko A.Yu.; Zorov Yu.N.; Titov V.V.; Gavrilov K.N. (Cultural Heritage and Modern Technologies)
Systematic control over the area of the seashore on the administrative border between the Donetsk People's Republic and the Rostov region has led to the accumulation of a collection of stone tools of the Middle Paleolithic and a collection of Pleistocene fauna. Loess-soil rocks of the Middle and Late Pleistocene are exposed in this area. All flint tools belong to the types of the Middle Paleolithic and were found in a redeposited state on the sea beach. Upper Cretaceous flint and alluvial flint were used for their production. The prospect of detecting a cultural layer at one of the material collection sites is noted. A recommendation was made on the organization of a targeted program for monitoring the state of archaeological heritage sites in the coastal zone of the Sea of Azov.